2018
DOI: 10.1177/0363546518801881
|View full text |Cite
|
Sign up to set email alerts
|

Does the Use of Psychotropic Medication Adversely Affect the Outcomes of Hip Arthroscopy?

Abstract: Background: Over the past decade, the use of psychotropic medications (PTMs) in the United States has doubled, and currently 20% of adults are taking 1 or more of these antidepressant, antianxiety, antipsychotic, or mood-altering medications. To date, however, the incidence of PTM use in patients undergoing hip arthroscopy and the results of hip arthroscopy in these patients have not been reported. Purpose: To determine the prevalence of PTM use in patients undergoing hip arthroscopy and to compare the outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“… a Unreported data points are denoted by a dash. For studies that did not report an overall mean age, 21,23,28 a weighted mean was calculated from the mean ages of the population subgroups that were reported. PROM, patient-reported outcome measure. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… a Unreported data points are denoted by a dash. For studies that did not report an overall mean age, 21,23,28 a weighted mean was calculated from the mean ages of the population subgroups that were reported. PROM, patient-reported outcome measure. …”
Section: Resultsmentioning
confidence: 99%
“…According to a survey of orthopaedic surgeons in 2017, many surgeons notice and potentially even discuss psychological health with their patients, but surgeons are less Unreported data points are denoted by a dash. For studies that did not report an overall mean age, 21,23,28 a weighted mean was calculated from the mean ages of the population subgroups that were reported. PROM, patient-reported outcome measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Additionally, it has been reported that 48% of patients are taking at least 1 psychotropic medication at the time of hip arthroscopy. 5 For patients undergoing hip arthroscopy, poor mental health has been correlated with worse preoperative patient-reported outcomes, 3,4,6 persistent postoperative pain, 7 and decreased postoperative patient reported outcomes (PROs). 4,6,[8][9][10][11] However, it remains unknown whether there is a potential bidirectional relationship between hip pain and poor mental health, as there is a paucity of research devoted to understanding how mental health disorders may be affected by surgical treatment of musculoskeletal conditions.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 , 4 Additionally, it has been reported that 48% of patients are taking at least 1 psychotropic medication at the time of hip arthroscopy. 5 For patients undergoing hip arthroscopy, poor mental health has been correlated with worse preoperative patient-reported outcomes, 3 , 4 , 6 persistent postoperative pain, 7 and decreased postoperative patient reported outcomes (PROs). 4 , 6 , 8 , 9 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%